(untitled) (Progressive Agriculture, 2014)
The possibility of using sugar mills wastewater/effluent in irrigation was evaluated by investigating the effects of wastewater on growth and yield of wheat (Triticum aestivum cv. Prodip). The experiment was conducted at North Bengal Sugar Mill site in Natore during December 2011 to March 2012. Three irrigation treatments (I1: irrigation with fresh/tubewell water, I2: irrigation with a mixture of fresh and wastewater at 1:1 ratio and I3: irrigation with wastewater) under a main factor and three fertilizer treatments (F0: no application of fertilizer, F1: half dose fertilizer and F2: full dose fertilizer) under a sub factor were evaluated. The experiment was laid out in a split-plot design with three replications of the treatments. Wheat was grown with three irrigations totaling 14 cm applied at 4, 26 and 43 days after sowing (DAS). Important growth and yield data of the crop were recorded. The highest grain yield of 1.829 t/ha was obtained under mixed water irrigation and the lowest grain yield of 1.469 t/ha was obtained under wastewater irrigation. The three irrigation treatments, however, provided statistically similar (p = 0.05) grain yield. For the interaction between irrigation and fertilizers, mixed water irrigation and full dose fertilizer application (I2F2) provided significantly higher grain yield (2.757 t/ha) than all other treatment combinations. The second highest yield, produced under freshwater irrigation and full dose fertilizer (I1F2), was statistically similar to the yield under wastewater irrigation and full dose fertilizer (I3F2). Results of this experiment thus exposed good prospects of irrigating wheat by sugar mills wastewater. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19174 Progress. Agric. 24(1&2): 211 - 218, 2013